2016
DOI: 10.1136/bjsports-2016-096760
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sport and occupational lower extremity injury risk through movement quality screening: a systematic review

Abstract: Background Identification of risk factors for lower extremity (LE) injury in sport and military/first-responder occupations is required to inform injury prevention strategies. Objective To determine if poor movement quality is associated with LE injury in sport and military/first-responder occupations. Material and methods Five electronic databases were systematically searched. Studies selected included: original data; analytic design; movement quality outcome (qualitative rating of functional compensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 34 publications
0
40
0
2
Order By: Relevance
“…Whitaker et al published a systematic review in 2016 investigating movement quality (15 out of 17 studies used FMS™ as the screening tool) and association with sport and occupational LE injury. 19 Based upon the quality of the individual studies included and mixed findings across studies, they reported that there was inconsistent evidence that poor movement quality was associated with increased risk of LE injury. 19 Two additional articles published in 2015 8,20 studying a similar population to the one in the current study, also showed similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitaker et al published a systematic review in 2016 investigating movement quality (15 out of 17 studies used FMS™ as the screening tool) and association with sport and occupational LE injury. 19 Based upon the quality of the individual studies included and mixed findings across studies, they reported that there was inconsistent evidence that poor movement quality was associated with increased risk of LE injury. 19 Two additional articles published in 2015 8,20 studying a similar population to the one in the current study, also showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…19 Based upon the quality of the individual studies included and mixed findings across studies, they reported that there was inconsistent evidence that poor movement quality was associated with increased risk of LE injury. 19 Two additional articles published in 2015 8,20 studying a similar population to the one in the current study, also showed similar results. The first article 20 investigated the FMS™ and found the FMS™ composite score to be a poor predictor of injury in a cohort of 167 male and female Division I collegiate athletes, with data collected across basketball, football, volleyball, cross country, track and field, swimming and diving, soccer, golf, and tennis athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Functional movement and sports performance tests are used to assess an athlete's conditions and prevent sportrelated injuries [4]. These tests could also be used as clinical tests to predict the risk of sports injury, because poor physical fitness, improper movement pattern, and insufficient sensorimotor control are vital factors in sports injuries [4,5]. Clinical screening tests, such as the functional movement screen (FMS), star excursion balance test (SEBT), and agility and muscle power tests, are commonly used to assess sports performance and injury prevention [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lower limb exercises are used in rehabilitation, performance assessment, injury screening and strength and conditioning (S&C) contexts [1][2][3]. Movement is deemed 'optimal' during these exercises when injury-risk is minimised and performance is maximised [4].…”
Section: Introductionmentioning
confidence: 99%